Increased emotional eating behaviors in children with autism: Sex differences and links with dietary variety. (April 2021) - Wallace, Gregory L; Richard, Emily; Wolff, Alexandra; Nadeau, Monica; Zucker, Nancy
Although food selectivity and so-called "picky" eating are well documented in autism spectrum disorder, emotion-linked eating has rarely been investigated. This study examined emotion-linked over- and under-eating based on parent ratings of these behaviors in 4- to 17-year-old children with autism spectrum disorder ( n = 190) as compared to same-age typically developing children ( n = 119). Children with autism spectrum disorder were rated as exhibiting both more emotional over-eating and more emotional under-eating behaviors than their typically developing peers. Furthermore, while sex differences in these emotional eating behaviors were not observed in the typically developing children, girls with autism spectrum disorder were rated as experiencing more emotional over-eating behaviors than boys with autism spectrum disorder. Finally, among all children with autism spectrum disorder, emotional over-eating was linked with increased consumption of sweet foods and decreased consumption of vegetables. These findings have implications for better understanding eating habits in children with autism spectrum disorder and suggest that emotional eating behaviors might have both immediate and downstream health impacts. Lay abstract: Although "picky" eating is well documented in autism spectrum disorder, emotional eating has rarely been investigated. This study examined emotional over- and under-eating based on parent ratings of these behaviors in 4- to 17-year-old children with autism spectrum disorder ( n = 190) as compared to same-age typically developing children ( n = 119). Children with autism spectrum disorder were rated as exhibiting both more emotional over-eating and more emotional under-eating behaviors than their typically developing peers. Furthermore, while sex differences in these emotional eating behaviors were not observed in the typically developing children, girls with autism spectrum disorder were rated as experiencing more emotional over-eating behaviors than boys with autism spectrum disorder. Finally, among all children with autism spectrum disorder, emotional over-eating was linked with increased consumption of sweet foods and decreased consumption of vegetables. These findings have implications for better understanding eating habits in children with autism spectrum disorder and suggest that emotional eating behaviors might have both immediate and downstream health impacts.